LIBS and FTIR–ATR spectroscopy studies of mineral–organic associations in saline soil - Ma, Fei; Du, Changwen; Zhang, Yiqiang; Xu, Xuebin; Zhou, Jianmin (Land degradation & development, 2021)
Direct characterization of the spatial distribution of elements and compound binding of salt–organic associations in soil is imperative for understanding the mechanisms of organic matter decomposition and nutrient release involved in soil degradation and development processes. However, traditional chemical methods would damage the chemical bonds in salt–organic associations, and modern spectroscopic techniques provide alternative options for resolving this problem. In this study, mid‐infrared‐attenuated total reflectance spectroscopy (FTIR–ATR) was used to obtain molecular group information; laser‐induced breakdown spectroscopy (LIBS) was applied to obtain microlevel distribution of elements, and two‐dimensional correlation spectroscopy (2DCOS) analysis was conducted to illustrate the binding combination features of mineral–organic associations in saline soil from the Hetao Irrigation District in China. The results showed that the distributions of Mg, Ca, Na, and K were heterogeneous at the microlevel; the spatial distributions of Mg and Ca showed a significant correlation (r = 0.90***), while K displayed a negative correlation with the soil organic matter (SOM) contents. In the soil with lower SOM contents, the elements were distributed at the top of the ablation area and enhanced with the increasing SOM content, which reflected the trends of the SOM layer thickness outside the mineral–organic associations at the microlevel. Furthermore, 2DCOS analysis suggested that the hydrogen bonds in silicate groups were stronger than those of organic functional groups, such as C=O/C=C, when combined with salt‐related compounds, and Mg, Ca, Na, and K did not originate from clay mineral compounds in saline soil but partially originated from deposited organic associations.